2019
DOI: 10.1001/jamanetworkopen.2019.7863
|View full text |Cite|
|
Sign up to set email alerts
|

Rates of New Persistent Opioid Use After Vaginal or Cesarean Birth Among US Women

Abstract: IMPORTANCE Research has shown an association between opioid prescribing after major or minor procedures and new persistent opioid use. However, the association of opioid prescribing with persistent use among women after vaginal delivery or cesarean delivery is less clear. OBJECTIVE To assess the association between opioid prescribing administered for vaginal or cesarean delivery and rates of new persistent opioid use among women. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study used national i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
121
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 41 publications
(146 reference statements)
4
121
1
Order By: Relevance
“…The primary outcome was new persistent opioid use (NPOU) after vaginal or cesarean delivery, defined as at least 2 pharmacy claims after discharge: !1 opioid prescription between 4 and 90 days postdischarge and !1 prescription between 91 and 365 days postdischarge. 5,14 This definition of NPOU is consistent with prior work, and represents a time when patients are expected to have recovered from their initial delivery episode.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…The primary outcome was new persistent opioid use (NPOU) after vaginal or cesarean delivery, defined as at least 2 pharmacy claims after discharge: !1 opioid prescription between 4 and 90 days postdischarge and !1 prescription between 91 and 365 days postdischarge. 5,14 This definition of NPOU is consistent with prior work, and represents a time when patients are expected to have recovered from their initial delivery episode.…”
Section: Methodsmentioning
confidence: 81%
“…1e4 This increased focus is warranted, as 1 in 75 women in the United States who fill an opioid prescription in the peripartum period will continue filling prescriptions up to 1 year postpartum. 5 In fact, exposure to postpartum opioids has been linked to new persistent use after delivery, independent of the type of birth (vaginal vs cesarean delivery), suggesting that the risk is inherent to the opioid prescription. 5 Less is known, however, about the long-term consequences of acute opioid prescribing during pregnancy, outside of the delivery episode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal age, parity, body mass index (BMI), maternal race/ethnicity, insurance status, and history of cesarean section were selected because they have been demonstrated to be associated with postoperative opioid use in the literature. [11][12][13] Year of delivery was included in the model given the rapid secular changes in opioid prescription recommendations during this time, as well as the potential for evolution in PMP accuracy. 7,14 Finally, we included county of residence as women who resided close to the border may have been more likely to fill their prescription in an adjoining state, thus making them undetectable in the Illinois PMP.…”
Section: Methodsmentioning
confidence: 99%
“…5 Overprescribing opioids is not without risk: 1.7% of patients who underwent vaginal delivery and 2.2% of cesarean deliveries had new persistent opioid use (>90 days after delivery) following initiation at delivery. 6 Numerous studies have shown signi cant racial and ethnic disparities in opioid prescribing practices. A Prescription Drug Monitoring Program (PDMP) study in California found 300% higher prescription rates in predominantly White communities compared to non-White communities.…”
Section: Introductionmentioning
confidence: 99%